Hubungan Perdagangan Majapahit dengan Tiongkok Abad XII - XIV - Siti Khusnul Khotimah; Yuliati Yuliati (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
The Majapahit Kingdom was a kingdom that had very good relations with foreign kingdoms in Southeast Asia and foreign kingdoms outside Southeast Asia. One of them is with China, which is a foreign kingdom in the East Asia region. This is because the Majapahit kingdom has a foreign policy called Mitreka Satata which means equal / equal. With this foreign policy, Majapahit was able to establish relationships with foreign kingdoms, one of which was China, which was a foreign kingdom outside Southeast Asia. Kakawin Desawarnana and Notes written by the Chinese themselves also briefly mention the very good relations between Majapahit and China in terms of trade. It was through this trade that Mitreka Satata's relationship between Majapahit and China could be formed and continued very well. In fact, because of trade, there are many Chinese and Majapahit people in social life. Therefore, this research will conduct an in-depth study of the Mitreka Satata relationship between Majapahit and China through existing historical sources.